2004
DOI: 10.1002/polb.10780
|View full text |Cite
|
Sign up to set email alerts
|

Brillouin scattering studies of polymeric nanostructures *

Abstract: For a range of applications, polymers are now being patterned into nanometer‐sized features. In these applications, the robust mechanical properties of the nanostructures are critical for performance and stability. Brillouin light scattering is presented as a nondestructive, noncontact tool used to quantify the elastic constants in such nanostructures. We demonstrate this through a series of thin films and parallel ridges and spacings (gratings) with ridge widths ranging from 180 to 80 nm. For the set of films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…BLS measurements have shown limited impact of confinement on linear PS and PMMA thin films. These results are consistent with the invariant modulus generally obtained for nanostructures using BLS . One potential explanation for the limited impact of confinement is the time scale associated with the BLS measurement due to the frequency of the radiation.…”
Section: Elastic Properties Of Polymer Glasses Under Confinementsupporting
confidence: 90%
“…BLS measurements have shown limited impact of confinement on linear PS and PMMA thin films. These results are consistent with the invariant modulus generally obtained for nanostructures using BLS . One potential explanation for the limited impact of confinement is the time scale associated with the BLS measurement due to the frequency of the radiation.…”
Section: Elastic Properties Of Polymer Glasses Under Confinementsupporting
confidence: 90%
“…The latter follows by ignoring F B in Eq. (7) and assuming K 0 (z) ∼ K 0,bulk , from which one can analytically derive an approximate inverse in distance variation from the surface behavior Figure 8 was used, while "simulation timescale" curve only fits the first 5 decades of data in Figure 8 to extract an exponent. Inset: Natural log-linear plot of the decoupling exponent versus location in the thick film.…”
Section: Interfacial Dynamic Decouplingmentioning
confidence: 99%
“…11 There are also recent examples in the literature of experimental methods for measuring the mechanical properties of thin and ultrathin polymer films, 5,12,13 the most prevalent being Brillouin light scattering (BLS). BLS has been used to measure the elastic constants of both supported 14,15 and free-standing 16 polymer films and features with thicknesses from 375 nm down to 29 nm, and it was observed that the high-frequency mechanical properties did not significantly change at these dimensions. Probing thinner free-standing films with BLS becomes difficult due to sample preparation and handing issues, while BLS measurements on thinner supported films are complicated by the presence of the substrate interface.…”
mentioning
confidence: 99%